2009
DOI: 10.1021/op900262f
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous, Facile and Selective Synthesis of Tetrabromobisphenol A using Potassium Tribromide: An Efficient and Renewable Brominating Agent

Abstract: An instantaneous method for the bromination of bisphenol A has been reported using potassium tribromide for the first time as an efficient brominating agent affording the corresponding tetrabromobisphenol A in a reaction time of only 5−10 min at ambient temperature in high yields (99%) and purity (>99%), free from reaction byproduct and having very low ionic impurities. Mild reaction conditions and simple workup provide a practical and commercially viable route for the synthesis of the largest selling flame re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Notably, compounds 411 and 412 were proved capable to release in aqueous media nitric oxide [230], a compound which has been shown to influence biofilm dispersal in P. aeruginosa [231] and to control biofilm properties at picomolar to nanomolar concentrations [232]. It was also observed that the most potent and nonbactericidal compound in the biofilm inhibition assay was fimbrolide-NO donor hybrid compound 411b, which showed a 73% decrease in biofilm biomass [230]…”
Section: Scheme 136 Synthesis Of Compound 416mentioning
confidence: 96%
See 3 more Smart Citations
“…Notably, compounds 411 and 412 were proved capable to release in aqueous media nitric oxide [230], a compound which has been shown to influence biofilm dispersal in P. aeruginosa [231] and to control biofilm properties at picomolar to nanomolar concentrations [232]. It was also observed that the most potent and nonbactericidal compound in the biofilm inhibition assay was fimbrolide-NO donor hybrid compound 411b, which showed a 73% decrease in biofilm biomass [230]…”
Section: Scheme 136 Synthesis Of Compound 416mentioning
confidence: 96%
“…Furthermore, in 2015, cadiolides C (359c) and A (359a) were synthesized by Franck and coworkers [213] by using the one-pot reaction of a-hydroxyketones, dioxinones and aryl aldehydes, which they had previously employed in the synthesis of cadiolide B (359b) [223]. As shown in Scheme 132, cadiolide C (359c) was obtained in 47% yield by reacting 1.0 equiv of a-hydroxyketone 359, 2.0 equiv of dioxinone 408 and 1.0 equiv of aldehyde 228 with 2.0 equiv of Et 3 N in toluene under microwave irradiation at 150 °C for 5 min and treatment of the resulting reaction mixture with 1 M HCl followed by BBr 3 -mediated Odemethylation of the resulting product [230].…”
Section: Scheme 128 Synthesis Of Rubrolide a Diacetate (390)mentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of 6,6-bis(3,5-dibromo-4-hydroxyphenyl)heptanoic acid (hapten). (24,26) 6,6-Bis(4-hydroxyphenyl)heptanoic acid (A [ Fig. 1], 3.14 g, 10 mmol) was dissolved in 40 mL acetic acid, then a solution of bromine (25.73 g, 0.16 mol) in 20 mL acetic acid was added dropwise.…”
Section: Preparation Of Haptenmentioning
confidence: 99%